Non-aflatoxigenic Aspergillus flavus as potential biocontrol agents to reduce aflatoxin contamination in peanuts harvested in Northern Argentina - Alaniz Zanon, Maria Silvina (2016)
Biological control is one of the most promising strategies for preventing aflatoxin contamination in peanuts at field stage. A population of 46 native Aspergillus flavus nonaflatoxin producers were analysed based on phenotypic, physiological and genetic characteristics. Thirty-three isolates were characterized as L strain morphotype, 3 isolates as S strain morphotype, and 10 isolates did not produce sclerotia. Only 11 of 46 non-aflatoxigenic isolates did not produce cyclopiazonic acid. The vegetative compatibility group (VCG) diversity index for the population was 0.37. For field trials we selected the non-aflatoxigenic A. flavus AR27, AR100G and AFCHG2 strains. The efficacy of single and mixed inocula as potential biocontrol agents in Northern Argentina was evaluated through a 2-year study (2014-2015). During the 2014 peanut growing season, most of the treatments reduced the incidence of aflatoxigenic strains in both soil and peanut kernel samples, and no aflatoxin was detected in kernels. During the 2015 growing season, there was a reduction of aflatoxigenic strains in kernel samples from the plots treated with the potential biocontrol agents. Reductions of aflatoxin contamination between 78.36% and 89.55% were observed in treated plots in comparison with the un-inoculated control plots. This study provides the first data on aflatoxin biocontrol based on competitive exclusion in the peanut growing region of Northern Argentina, and proposes bioproducts with potential use as biocontrol agents.